2002
DOI: 10.1128/mcb.22.12.4113-4123.2002
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Inhibition Enhances Glucocorticoid Receptor Transactivation and Alters Its Subnuclear Trafficking

Abstract: The ubiquitin-proteasome pathway regulates the turnover of many transcription factors, including steroid hormone receptors such as the estrogen receptor and progesterone receptor. For these receptors, proteasome inhibition interferes with steroid-mediated transcription. We show here that proteasome inhibition with MG132 results in increased accumulation of the glucocorticoid receptor (GR), confirming that it is likewise a substrate for the ubiquitin-proteasome degradative pathway. Using the mouse mammary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
114
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 53 publications
13
114
0
3
Order By: Relevance
“…It has recently been demonstrated that inhibition of proteosomal degradation enhances the transcriptional response mediated by some nuclear receptors (Blanquart et al, 2002;Deroo et al, 2002;Pollenz, 2002) and the Ets protein E1AF (Takahashi et al, 2005). We show here that blocking protein turnover with the proteasome inhibitor ALLN or MG132 also induces a change in ERM transcriptional activity.…”
Section: Discussionsupporting
confidence: 53%
“…It has recently been demonstrated that inhibition of proteosomal degradation enhances the transcriptional response mediated by some nuclear receptors (Blanquart et al, 2002;Deroo et al, 2002;Pollenz, 2002) and the Ets protein E1AF (Takahashi et al, 2005). We show here that blocking protein turnover with the proteasome inhibitor ALLN or MG132 also induces a change in ERM transcriptional activity.…”
Section: Discussionsupporting
confidence: 53%
“…Hence, it is possible that the UPP may be playing opposite roles with respect to PR and GR. For GR it has been recently demonstrated that proteasome inhibition causes the promoter occupancy of GR to increase and receptor mobility to decrease (55). Although no mechanistic studies have been reported to date for VDR, it appears that a similar mechanism might be operating.…”
Section: Ubiquitin-proteasome Pathway and Nhr Transcriptional Regulationmentioning
confidence: 99%
“…On the contrary, it appears that ligand may not be acting as a signal in case of VDR and AR, since these receptors are stabilized upon binding to their ligands. Yet, another scenario is with the GR, which undergoes ligand-dependent down regulation but at the same time proteasome inhibitors enhance its transcriptional activity (55). Therefore, the precise role of the proteasome in NHR transcription is quite complex and far from clear.…”
Section: Ubiquitin-proteasome Pathway and Nhr Transcriptional Regulationmentioning
confidence: 99%
“…3). The receptor is ubiquitinated at a conserved lysine residue located in a PEST degradation motif at the end of the NTD, and this modification targets the receptor for degradation by the proteasome (88,89). Mutation of this lysine residue blocks ligand-dependent down-regulation of GR␣ and enhances its transcriptional activity on reporter genes (89).…”
Section: Post-translational Modification Of Gr Isoformsmentioning
confidence: 99%